Black diamond : the story of the Negro baseball leagues - McKissack, Pat, 1944-; McKissack, Fredrick, Jr. (New York : Scholastic, 1994)
Traces the history of baseball in the Negro Leagues and its great heroes, including Monte Irwin, Buck Leonard, and Cool Papa Bell.
Includes bibliographical references (p. 178) and index.
G12
Keywords: Negro leagues -- History -- Juvenile literature; Baseball -- United States -- History -- Juvenile literature; Negro leagues -- History; Baseball -- History; African Americans -- Biography